2013
DOI: 10.3389/fncom.2013.00019
|View full text |Cite
|
Sign up to set email alerts
|

Are muscle synergies useful for neural control?

Abstract: The observation that the activity of multiple muscles can be well approximated by a few linear synergies is viewed by some as a sign that such low-dimensional modules constitute a key component of the neural control system. Here, we argue that the usefulness of muscle synergies as a control principle should be evaluated in terms of errors produced not only in muscle space, but also in task space. We used data from a force-aiming task in two dimensions at the wrist, using an electromyograms (EMG)-driven virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 66 publications
(106 reference statements)
6
131
0
Order By: Relevance
“…It is reported that there are similarities in the muscle synergies when performing the same movement across subjects. Several authors reported muscle synergies when walking (Clark et al, 2010;Dominici et al, 2011;Ivanenko et al, 2004;Neptune et al, 2009;Oliveira et al, 2014), walking with perturbations (Ivanenko et al, 2005) or performing other tasks (Rugy et al, 2013). Clark et al (2010) applied the muscle synergy analysis in post-stroke injured subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that there are similarities in the muscle synergies when performing the same movement across subjects. Several authors reported muscle synergies when walking (Clark et al, 2010;Dominici et al, 2011;Ivanenko et al, 2004;Neptune et al, 2009;Oliveira et al, 2014), walking with perturbations (Ivanenko et al, 2005) or performing other tasks (Rugy et al, 2013). Clark et al (2010) applied the muscle synergy analysis in post-stroke injured subjects.…”
Section: Introductionmentioning
confidence: 99%
“…One of these components (parallel to the UCM, V UCM ) does not affect the performance variable, whereas the other one (orthogonal to the UCM, V ORT ) does. There are other methods that study the structure of variance (reviewed in de Rugy et al 2013;Tresch and Jarc 2009; Tresch et al 2006), but the UCM-based analysis is particularly appropriate for our study because it provides direct links between variance in two spaces, those of a particular performance variable and of elemental variables.A scheme combining the principle of abundance, the hierarchical control scheme, the idea of synergies, the UCM hypothesis, and control with RC (Latash 2010) allows making predictions with respect to phenomena of equifinality at different levels of analysis of a redundant system. In particular, this scheme predicts that a transient perturbation may be expected to result in equifinality at the level of task-related performance variables defined by an invariant RC at the highAddress for reprint requests and other correspondence: M. L. Latash,…”
mentioning
confidence: 99%
“…One of these components (parallel to the UCM, V UCM ) does not affect the performance variable, whereas the other one (orthogonal to the UCM, V ORT ) does. There are other methods that study the structure of variance (reviewed in de Rugy et al 2013;Tresch and Jarc 2009; Tresch et al 2006), but the UCM-based analysis is particularly appropriate for our study because it provides direct links between variance in two spaces, those of a particular performance variable and of elemental variables.…”
mentioning
confidence: 99%
“…Once the decoder was trained, it is used in real time to estimate the multijoint angles and map them to output of myoelectric interface. Moreover, linear combinations of synergies are capable of describing complex force and motion patterns in reduced dimensions [33]. Therefore the robust representations of synergies within the control scheme can generate flexible gaits for other complex motions, such as hopping and running with user's intent.…”
Section: Resultsmentioning
confidence: 99%